2-{1- 2-((2-Ammonioethyl){2- 1-(5-chloro-2-hydroxyphenyl)ethylideneamino ethyl}amino)ethyliminio ethyl}-4-chlorophenolate trifluoroacetate - Lee, S.M.; Ng, S.W.; Lo, K.M.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
In the title ion-pair, C(22)H(29)Cl(2)N(4)O(2)(+)center dot C(2)F(3)O(2)(-), ammonium-carboxylate N-H center dot center dot center dot O hydrogen bonds link two cations and two anions about a centre of inversion to generate a hydrogen-bonded tetramer. In the cation, one of the imino N atoms is protonated and donates a hydrogen bond to the O atom of the adjacent chlorophenyl ring. The other imino N atom acts as a hydrogen-bond acceptor from a phenolate O atom.